2014
DOI: 10.1111/apa.12711
|View full text |Cite
|
Sign up to set email alerts
|

Caesarean delivery is associated with childhood general obesity but not abdominal obesity in Iranian elementary school children

Abstract: Our results suggest that Caesarean delivery is adversely associated with general childhood obesity, but not abdominal obesity. This provides support for recommending vaginal births, unless contraindicated. Further research in large populations is required to confirm these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…The findings of our study were in accordance with other studies which controlled maternal BMI [16] and socioeconomic status [17, 29]. …”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The findings of our study were in accordance with other studies which controlled maternal BMI [16] and socioeconomic status [17, 29]. …”
Section: Discussionsupporting
confidence: 93%
“…In addition, our study is lacking information on antibiotics use during pregnancy as potential confounder; it has been observed that maternal exposure to antibiotics in second or third trimester of pregnancy increased the risk of childhood obesity at age 7 years [19]. However, this limitation is shared with other studies which reported significant association between delivery mode and overweight or obesity [9, 17, 20]. …”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The selection process of participants is completely described elsewhere [18]. After exclusion of participants with special dietary restrictions, prohibition or restriction of food intake in the previous year ( n  = 50), congenital diseases ( n  = 2), and not having complete data on food insecurity, anthropometric measures, or covariates ( n  = 332), 587 participants remained for the current analysis.…”
Section: Methodsmentioning
confidence: 99%
“…There are few studies that report on motor development outcomes in children born from Caesarean section birth. As previously identified by Hands and colleagues, there is some evidence of lower intellectual outcomes and more recent research has reported higher levels of adiposity in children born via Caesarean from infancy to adolescence . The incidence of asthma and allergies in children born via Caesarean has been scrutinised by several international studies with varying results .…”
Section: Discussionmentioning
confidence: 97%